THEORETICAL FOUNDATIONS OF ECONOMIC SECURITY AND ITS FEATURES IN THE CONSTRUCTION INDUSTRY (Development Service Industry Management, 2024)
The article examines the dual challenge faced by construction enterprises in the context of the COVID-19 pandemic and the military aggression of the Russian Federation against Ukraine. It highlights the serious obstacles these events pose to the economic security of enterprises, considering the complex impact of both factors. The study reviews previous publications exploring the theme of economic security of enterprises and provides a concise summary in a table forcomparing the definition of the term "Enterprise Economic Security System." The classification of threats to the country's economic security, both internal and external, is presented. The article delves into the issues of economic security as a system for ensuring stability.The author identifies factors that can negatively impact the economic security of construction industry enterprises, including rising costs of occupational safety, logistical challenges, and reduced demand for construction services. Emphasis is placed on the need for strategic management to support the resilience of enterprises in these challenging conditions. The author subsequently proposes comprehensive strategies and tools for crisis management in the industry, including the implementation of effective occupational safety systems, the use of technology to enhance logistics, and market diversification. The importance of adapting business models to economic instability is underscored, with a focus on flexibility and rapid response to changes in the internal and external environment. According to the author, this is crucial for ensuring stability and successful operations in the face of a dual crisis. In conclusion, the article emphasizes the importance of a systematic approach to crisis management in the construction industry, allowing not only survival during crises but also fostering growth and long-term stability.
Keywords: Economic Security; Construction Industry; Crisis Management